Comparison outcome of open and close reduction treatments for parasymphysis mandibular fractures - Fardhani, Annisa; Rizqiawan, Andra; Mulyawan, Indra; Anugraha, Ganendra (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: Mandibular fracture is a condition of mandibular discontinuity. The treatment aims to reconstruct the appropriate anatomical position. Reduction is the process of repositioning fracture fragments to their original anatomical positions, which can be done by open and closed techniques. Open reduction is more invasive, and the possibility of nerve or blood vessel injury and infection postoperatively is greater. Closed reduction also has postoperative complications such as muscle atrophy, periodontal tissue and mucosa damage, speech disorders, and nutritional disorders. In the final determination of the treatment plan, the advantages, disadvantages, and risks of each treatment and the risk of complications should be sufficiently discussed with patients and the patient's guardians. Purpose: This case aims to compare the outcome of open reduction and internal fixation (ORIF) with closed reduction treatment in the management of mandibular parasymphysis fractures. Cases: Two case studies of mandibular parasymphysis fractures. Clinically, each patient had mandibular displacement and occlusion disturbance before treatment. Case Management: The treatment plan is considered by the patient's age and fracture type. One patient received ORIF, and the other received close reduction treatment with gradual repositioning. Malocclusion after treatment was absent in both cases. Conclusion: Open reduction is recommended for displaced parasymphysis fractures. In cases where the open reduction technique cannot be performed, the closed technique can be an alternative, especially on non-displaced or minimally displaced parasymphysis fractures.